2008
DOI: 10.1088/0953-8984/21/1/015803
|View full text |Cite
|
Sign up to set email alerts
|

Vacancies in wurtzite GaN and AlN

Abstract: Vacancies in wurtzite GaN and AlN are studied using a computational method which is based on the density functional theory (DFT) and takes into account the errors arising from use of finite-sized supercells and the DFT band gap underestimation. Negatively charged N vacancies in GaN and AlN are found to be stable, with formation energies similar to and higher than those of Ga and Al vacancies in n-type material under Ga-and Al-rich growth conditions, respectively. The localization and energies of the defect lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 19 publications
(39 reference statements)
5
60
1
4
Order By: Relevance
“…E F is the Fermi level, referenced to the valence-band maximum in the bulk and E V is the energy of the valence-band maximum (VBM) of the defect. If the formation energy is calculated in the infinite crystal, then VBM of the defect is equal to the VBM of the bulk (pristine) system [29]. The thermal transition energies ε(q/q') is defined as the Fermi energy where the lowestenergy charge state changes from q to q' as E F rises in the gap.…”
Section: Computational Detailsmentioning
confidence: 99%
“…E F is the Fermi level, referenced to the valence-band maximum in the bulk and E V is the energy of the valence-band maximum (VBM) of the defect. If the formation energy is calculated in the infinite crystal, then VBM of the defect is equal to the VBM of the bulk (pristine) system [29]. The thermal transition energies ε(q/q') is defined as the Fermi energy where the lowestenergy charge state changes from q to q' as E F rises in the gap.…”
Section: Computational Detailsmentioning
confidence: 99%
“…However, when supercells of sufficiently large sizes are used, the interaction of the defect with the spurious periodic images and with the jellium background will become negligible. 32 Hence we used 192-atom supercells in most cases and, also, supercells with 256 atoms in some selected cases. Finite-size effects are taken into account in the formation energy calculations by considering the change in configuration energy (E conf = E def tot − E bulk tot ) and extrapolating to infinity.…”
Section: A Defect Formation Energymentioning
confidence: 99%
“…This is in reasonable agreement with our calculation. Third, the formation energies of isolated Al vacancies become very low as the Fermi-level approaches the conduction band [24][25][26]. This explains why the VL A band emerges only in n-type AlN, while it is absent in insulating material.…”
Section: àmentioning
confidence: 99%
“…Another possibility is oxygen, incorporating on nitrogen site, i.e. O N , whose concentration is typically in the order of 10 18 N ) at about 120 meV below the conduction band [26]. In contrast, Zhang et al [24], found that nitrogen vacancies only incorporate as deep donors, more than 1 eV below the conduction band, whereas Stampfl et al and Van de Walle [25] claimed that V N is forming a shallow donor in AlN.…”
Section: àmentioning
confidence: 99%